(untitled) - Wu, Ge (Hoboken, N.J., 2010)
The first comprehensive, integrated treatment of the subject, Assay Development: Fundamentals and Practices covers the essentials and techniques involved in carrying out an assay project in either a biotechnology/drug discovery setting or a platform setting.
Thử nghiệm sinh học
Keywords: Thử nghiệm sinh học,Biological assay